Effect of mesenchymal stem cells on the vascularization of the artificial site for islet transplantation in rats - Fabryova, E; Jirak, D; Girman, P; Zacharovova, K; Galisova, A; Saudek, F; Kriz, J (Transplantation proceedings, 2014)
An adequate vascularization of the artificially created cavity is crucial for subsequent transplantation of isolated pancreatic islets. In a reported study, dynamic contrast-enhanced magnetic resonance imaging was used to assess the effect of mesenchymal stem cells on neoangiogenesis within connective tissue surrounding an implantable biocompatible device. The signal increase detected after injection of magnetic resonance contrast agent in each target region was considered to be an effect of contrast agent, which was related to the blood supply. To minimize the influence of variability in contrast agent application, all outcomes measured in the implanted devices were normalized to the signal intensity of kidney tissue. When supported by mesenchymal stem cells, the mean signal increase intra-abdominally was 42%, 41%, and 64% and within subcutaneously implanted devices was 23%, 54%, and 52% of that measured in kidney.
Keywords: Magnetic Resonance Imaging; kontrastní látky; omentum; magnetická rezonanční tomografie; gadolinium; fyziologická neovaskularizace; Contrast Media; Gadolinium; Mesenchymal Stem Cell Transplantation; ledviny; Kidney; Tissue Scaffolds; krysa rodu Rattus; Islets of Langerhans Transplantation; Organometallic Compounds; zvířata; organokovové sloučeniny; transplantace Langerhansových ostrůvků; Omentum; transplantace mezenchymálních kmenových buněk; tkáňové podpůrné struktury; Male; Rats; Animals; mužské pohlaví; Neovascularization, Physiologic